IMPROVEMENT OF SCIENCE LEARNING OUTCOMES CLASSIFICATION MATERIAL ANIMALS BASED ON THEIR DIET THROUGH INTERACTIVE LEARNING MODEL TYPE OF PICTURE AND PICTURE - Isnaeni, Nurul (Journal of Higher Education and Academic Advancement, 2025)
Objective: The purpose of this study was to obtain data on improving science learning outcomes on the classification of animals based on the type of food through the picture and picture type interactive learning model. In class IV students at SDN Teluk Pucung III, North Bekasi. Method: This research method uses classroom action research with a target research design. This research was conducted in 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The research time was 3 months, from April 2023 to June 2023 with 35 research subjects, while data was collected through tests, observations, interviews and documentation. Results: The results showed that there was an increase in science learning outcomes in fourth grade students. This is evidenced by the average results of the Science test in each cycle, namely the pre-action average value = 64.1, the first cycle = 72.3 and the second cycle = 8.64. While research can be said to be successful if the completeness results obtained by students reach the average criteria determined by the researcher, namely 75%. Novelty: This study concludes that learning science materials for classifying animals based on the type of food through the picture and picture type interactive learning model for improving student learning outcomes at SDN Teluk Pucung III, Bekasi.